Potential, Prospect and Investment Policies in Surabaya City - S. Muljaningsih; I. M. Hendrati; M. Wahed (Future Science)
Development planning covers all aspects including investment. To process potential economic potential to become real one of the most important means is the development of investment because with the development of investment will encourage employment, increase national/regional income and increase the quality of human resources which will ultimately create public welfare. Potency. Realization of investment during the period 2011-2017 in the city of Surabaya was relatively volatile with an upward trend, the realization always exceeded the target that had been set, namely with the achievement of 109.60%. Based on the results of the study, of the 17 (seventeen) sectors in the GRDP which are the potential sectors of investment in the City of Surabaya are the Industry and Trade and Repair sectors; as well as hotels and restaurants. The potential realization is based on the realization of the number of projects, the amount of employment and the amount of PMA and PMDN investments in the sector. While policies that can be applied in order to improve the investment climate in Surabaya are bureaucratic efficiency and corruption prevention; infrastructure improvement; tax and retribution policy; expansion of access to finance; and increasing domestic and foreign investment cooperation and promotion.